English for Specific Purposes: A Need Analysis at The Second Semester of Physics Education Students of IAIN Raden Intan Lampung in The Academic Year of 2015/2016 - Indrasari, Nunun (Universitas Islam Negeri Raden Intan Lampung, 2016)
The objectives of this study are: (1) to explore the problems faced by physics students in ESP class, and (2) to reveal the needs of physics students in ESP class. The study was conducted in IAIN Raden Intan Lampung from April to June 2016. The participants of the study were 50 students at the second semester of physics education students of IAIN Raden Intan Lampung, and 4 ESP lecturers who taught ESP for physic students in the academic year of 2015/2016. The data were in the form of qualitative data which are taken from the interview and the questionnaire. The data were about the problems which are usually faced by physics students during learning English and the students’ needs and wants towards the ESP course in IAIN Raden Intan Lampung. The findings describe the students’ need of ESP for physics students, the lecturers’ view points on the practice of ESP instructions, and descriptions of problems commonly faced by ESP students in Physics Education of IAIN Raden Intan Lampung.